Corporate Social Responsibility and Firms’ Financial Performance: A Study of Nigerian Consumer Goods Companies - Emamoke Jarikre Victor; Omodero Cordelia Onyinyechi (Economics and Business)
The study is based on corporate social responsibility and financial performance of companies in Nigeria. The study focuses on the issues and ideologies that surround the practices of corporate social responsibility by consumer goods companies in Nigeria. The main objective of the study is to explore the impact of corporate social responsibility on profit after tax, earnings per share and net asset per share of listed consumer goods companies in Nigeria. The study adopts ex-post facto research design. Data were collected from financial reports of five listed consumer goods companies in Nigeria for a period of 5 years from 2015 to 2019. The financial reports and the hypotheses were statistically analysed using the panel data regression analysis. The results revealed a positive but insignificant effect of corporate social responsibility on profit after tax, earnings per share and net asset per share. According to the findings of the study, corporate social responsibility requires more attention and commitment from corporations because it ensures benefits other than profits which in the end boost financial performance.